Digital ion trap mass analysis of high mass protein complexes using IR activation coupled with ion/ion reactions - Lee, Kenneth W. (Int J Mass Spectrom, 2020)
Native mass spectrometry (MS) focuses on measuring the masses of large biomolecular complexes and probing their structures. Large biomolecular complexes are readily introduced into mass spectrometers as gas-phase ions using electrospray ionization (ESI); however, the ions tend to be heavily adducted with solvent and salts, which leads to mass measurement errors. Various solution clean-up approaches can reduce the degree of adduction prior to introduction to the mass spectrometer. Gas-phase activation of trapped ions can provide additional adduct reduction, and charge reduction ion/ion reactions increase charge state separation. Together, gas-phase activation and charge reduction can combine to yield spectra of well separated charge states for improved mass measurements. A simple gas-phase collisional activation technique is to apply a dipolar DC (DDC) field to opposing electrodes in an ion trap. DDC activation loses its efficacy when ions are trapped at low q values, which is true of the high m/z ions generated by charge reduction ion/ion reactions. Digital ion trapping (DIT) readily traps high m/z ions at higher q values by varying trapping frequency rather than amplitude, but the low frequencies used to trap high m/z ions also decreases the efficacy of DDC activation. We demonstrate here using ions derived from GroEL that IR activation of ions shows no discrimination against high m/z ions trapped with DIT, because they can be focused equally well to the trap center to interact with the IR laser beam. Following pump out of excess background gas, IR activation can also induce efficient dissociation of the GroEL complex. This work demonstrates that IR activation is an effective approach for ion heating in native MS over the unusually wide range of charge states accessible via gas-phase ion/ion reactions.